2009
DOI: 10.1186/1756-0500-2-165
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium sulphate therapy in eclampsia: the Sokoto (ultra short) regimen

Abstract: BackgroundContinuing the administration of magnesium sulphate for 24 hours after the last fit in patients with eclampsia is at best empirical. The challenge of such a regimen is enormous in low-resource countries. The objective of this study was to assess the effectiveness of an ultra-short regimen of magnesium sulphate in eclamptics.FindingsThis was a prospective, cohort study of eclamptic patients admitted between July 2007 and June 2008 that were given 4 grams magnesium sulphate intravenously and 10 grams i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
32
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 22 publications
4
32
0
Order By: Relevance
“…Several studies investigated the role of only single loading dose of MgSO 4 in managing hypertensive disorders in pregnancy [17][18][19][20][21][22]. All of them were carried out in low resource countries like Pakistan [17,18], Bangladesh [19], Nepal [20], Nigeria [21,22] and Egypt [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies investigated the role of only single loading dose of MgSO 4 in managing hypertensive disorders in pregnancy [17][18][19][20][21][22]. All of them were carried out in low resource countries like Pakistan [17,18], Bangladesh [19], Nepal [20], Nigeria [21,22] and Egypt [23].…”
Section: Discussionmentioning
confidence: 99%
“…All of them were carried out in low resource countries like Pakistan [17,18], Bangladesh [19], Nepal [20], Nigeria [21,22] and Egypt [23]. Noor et al [17] conducted a study on MgSO 4 in women with eclampsia and preeclampsia at Peshawar, Pakistan in which majority of the patients received only loading dose and 5g intramuscular dose was repeated only if the patient had convulsions [17].…”
Section: Discussionmentioning
confidence: 99%
“…Efficacy of Ultra short regimen (4 grams magnesium sulphate intravenously and 10 grams intramuscularly as the sole anticonvulsant agent) was used in a study conducted by Ekele BA et al and was effective in controlling fits in 92.6% of cases in the study group. 6 Another study conducted by JR Chaudhary et al showed no significant difference in recurrence of convulsion, maternal mortality, serious maternal morbidity, perinatal morbidity or mortality between the low dose i.v regimen of magnesium sulphate infusion (0.6 gm/h) and standard pritchard regimen. 4 Using low dose regimens will not only decrease the risk of maternal toxicity and fetal side effects but also decrease the cost of therapy and increase its safety for rural low resources setting where magnesium sulphate level monitoring is not readily available.…”
Section: Introductionmentioning
confidence: 99%
“…4 Using low dose regimens will not only decrease the risk of maternal toxicity and fetal side effects but also decrease the cost of therapy and increase its safety for rural low resources setting where magnesium sulphate level monitoring is not readily available. 6 A low dose magnesium sulphate may be more appropriate in cases of mild renal impairment which is usually present in these patients. A study conducted by MR begum et al had explained that the low BMI of the women in Dhaka explains the efficacy of low dose regimen in controlling fits.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Ekele et al in his study demonstrated that limiting the dosage of magnesium sulphate to 14 grams loading dose (4 grams intravenous and 10 grams intramuscular) was effective in controlling fits in 92.6% of cases. 17 With Pritchard's regime, 3 (6%) patients had absent knee jerks, but no such drug toxicity was seen with low dose magnesium sulphate therapy. This is in accordance with Dasgupta who showed that magnesium toxicity was less with low dose therapy than with standard regimen.…”
Section: Discussionmentioning
confidence: 99%